2022
DOI: 10.1128/mmbr.00181-21
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Microbiota of the Female Reproductive Tract in Gynecological and Reproductive Health

Abstract: The microbiome of the female reproductive tract defies the convention that high biodiversity is a hallmark of an optimal ecosystem. Although not universally true, a homogeneous vaginal microbiome composed of species of Lactobacillus is generally associated with health, whereas vaginal microbiomes consisting of other taxa are generally associated with dysbiosis and a higher risk of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 289 publications
5
35
0
Order By: Relevance
“…This suggests that stronger interbacterial interactions help them escape the antibiotic, which is in line with the findings of Gustin's study (Gustin et al, 2022). Lactobacillus, which possessed higher abundance in the cured samples, had the most negative correlations due to the ability of Lactobacillus to secrete lactic acid and bactericidal substances, which inhibit the growth of BV-associated pathogenic bacteria (Zhu et al, 2022). In addition, we found Ureaplasma parvum enriched in cured samples both in the short-term cured group and in the long-term cured group and a significant negative correlation with certain BV-associated bacteria, which is consistent with the study of Xiao et al (Xiao et al, 2019).…”
Section: Differences In Vaginal Microbiome Between the Short-term Cur...supporting
confidence: 86%
“…This suggests that stronger interbacterial interactions help them escape the antibiotic, which is in line with the findings of Gustin's study (Gustin et al, 2022). Lactobacillus, which possessed higher abundance in the cured samples, had the most negative correlations due to the ability of Lactobacillus to secrete lactic acid and bactericidal substances, which inhibit the growth of BV-associated pathogenic bacteria (Zhu et al, 2022). In addition, we found Ureaplasma parvum enriched in cured samples both in the short-term cured group and in the long-term cured group and a significant negative correlation with certain BV-associated bacteria, which is consistent with the study of Xiao et al (Xiao et al, 2019).…”
Section: Differences In Vaginal Microbiome Between the Short-term Cur...supporting
confidence: 86%
“…These pathogenic bacteria could cause tissue injury and increased vulnerability to urine incontinence by causing persistent in ammation de ned by neutrophil in ltration and immune molecules and cytokines activation. [11,29]. In our study, the vaginal microbiota of SUI patients showed a stronger correlation with bacterial vaginitis and a dysbiosis of microbial communities.…”
Section: Discussionsupporting
confidence: 51%
“…4d and e). Maternal factors, e.g., microbial infections, have been reported to in uence the gestational age at delivery or the risk for preterm birth 35 and could subsequently impact the health state, e.g., the NICU admission, birthweight (Fig. 3c and 4c), and the development of the neonatal immune system 50 .…”
Section: Discussionmentioning
confidence: 99%